Conceptual basis of color-dynamic composition of table by S.-A. Madyar and oculomotor of the visual perception of chromaticity - S.-A. I. Madyar; E. V. Moiseyenko; O. E. Kovalevska (Ukrainian Antarctic Journal, 2016)
The paper examines the conceptual bases of construction of color-dynamic table by S.-A. Madyar, taking into account the laws of color perception dynamics. Were conducted the pilot studies of the motor function of the human eyeball in the process of the visual perception of the color spectrum. It has been shown that the individual preferences of visual perception chromatic tables characterized by objective indicators of oculomotor activity that allow to evaluate the dynamic stability of the pupils in the preferred sectors of color. Was found that color preferences are depend on the options psychophysiological state of levels of tonus (intellectual, emotional, physical) and the person’s age. It is expected that the identification features of activation of motor function of the human eyeball with the visual perception of color-dynamic compositions opens up the possibility of purposeful use of the tables by S.-A. Madyar for assessment of psycho-physiological status and bio-regulation.